Analyzing public expenditure benefit incidence in health care: Evidence from India - Lekha S. Chakraborty; Yadawendra Singh; Jannet Farida Jacob (Levy Economics Institute of Bard College, 2013)
The effectiveness of public spending remains a relatively elusive empirical issue. This preliminary analysis is an attempt, using benefit incidence methodology, to define the effectiveness of spending at the subnational government level in India's health sector. The results reveal that the public health system is seemingly more equitable in a few states, while regressivity in the pattern of public health-care utilization is observed in others. Both results are to be considered with caution, as the underdeveloped market for private inpatient care in some states might be a factor in the disproportionate crowding-in of inpatients, making the public health-care system simply appear more equitable. However, patients voting with their feet and choosing better, private services seems evident only in the higher-income quintiles. Results also suggest that polarization is distinctly evident in the public provisioning of health-care services, though more related to inpatient, rather than ambulatory, services.
Keywords: H51; H75; I14; 330; effectiveness of public spending; benefit incidence